IMPACT OF SOWING TECHNIQUES AND NITROGEN FERTILIZATION ON CASTOR BEAN YIELD IN SALT AFFECTED SOILS - M. Jamil; S. S. Hussain; M. Amjad Qureshi; ǂ S. M. Mehdi; M.Q. Nawaz (Journal of Animal and Plant Sciences, 2017)
Irrigation induced soil salinity or secondary salinization has become severe threat to food security through deterioration of soil and reduction of crop yields. An integrated management approach is direly needed to combat the salinity stress by reclamation of soil through amendments, agronomic / engineering approaches, scheduling of irrigation schemes, proper drainage and farming practices. Another approach is the introduction of minor crops on marginal lands by different management practices. Castor bean (Ricinus communis L.) belongs to the family Euphorbiaceae grown as non-edible oil seed crop with enormous significance. Experiments were conducted to assess the best dose of fertilizer and different sowing methods to popularize the non-traditional crop among the farming community under salt affected soils during 2010-13. Treatments included in the study were i.e. N levels (90 and 60 kg N ha-1) and sowing methods (ridge, drill and broadcast sowing) laid out in split plot arrangement with three replications. Results exhibited that the maximum plant height (316.7 cm), number of branches plant-1 (13.00), number of nodes plant-1(25.03), 100 seed weight (29.07 g) and seed yield (2.072 t ha-1) obtained from ridge sowing method with 90 kg N ha-1 compared to the rest of treatments. Moreover, ridge sowing method with 90 kg N ha-1 proved to be the effective technique for successful production of castor bean on salt affected soil. The ridge and drill sowing showed least value of ECe and SAR at both levels of N as compared to broadcast sowing.
Keywords: Sowing methods; fertilizer; Ricinus; yield and yield components